Factor that influence in implementation of practices for IT alignment strategic in the public sector - Díaz, Juan (2019)
The low level of strategic alignment of IT that exists in many entities of the public sector causes these organizations do not reach a high performance, in spite of the implementations of practices and of the management given by the government of IT. For this reason, studies have been made of the factors that influence the implementation of IT governance and its areas, among which the strategic alignment of IT stands out. However, the factors that influence each of the practices that lead to strategic alignment have not yet been identified, which is important to know as each practice shapes the IT strategy of the organization, and this will allow taking actions to mitigate the factors negative or enhance the positive ones, and as a consequence obtain a good strategic alignment. In this work we have identified 16 implementation factors, 10 practices for the strategic alignment of IT, in the context of the public sector, and 48 influence relationships (factor → practice). An empirical study on 50 executives from the public sector validates 41 of the 48 relationships proposed with a rating between “High” and “Very High”, at 95% confidence through the t-Student test.